2001
DOI: 10.1074/jbc.m104353200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate May Be a Major Component of Plasma Lipoproteins Responsible for the Cytoprotective Actions in Human Umbilical Vein Endothelial Cells

Abstract: Sphingosine 1-phosphate (S1P), a novel lipid mediator, is concentrated in the fraction of lipoproteins that include high density lipoprotein (HDL) and low density lipoprotein (LDL) in human plasma. Here, we show that oxidation of LDL resulted in a marked reduction in the S1P level in association with a marked accumulation of lysophosphatidylcholine (LPC). We therefore investigated the role of the lipoprotein-associated lipids especially S1P in the lipoprotein-induced cytoprotective or cytotoxic actions in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
183
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(188 citation statements)
references
References 34 publications
5
183
0
Order By: Relevance
“…phosphatidylinositol-specific phospholipase C and phosphatidylcholine-specific phospholipase D) (15,16), and mobilization of intracellular Ca 2ϩ (16). However, work from our laboratory and other laboratories has demonstrated that these signaling events are generally not related to cholesterol efflux but rather account for other potentially anti-atherogenic effects of HDL, such as stimulation of cell proliferation or inhibition of apoptosis (12)(13)(14)16). Moreover, induction of these signaling pathways is not linked to apoA-I but rather to active lipids carried by HDL (10 -14, 16).…”
Section: Fig 2 Inhibition Of Cdc42 Suppresses Apoa-i-induced Cholesmentioning
confidence: 99%
“…phosphatidylinositol-specific phospholipase C and phosphatidylcholine-specific phospholipase D) (15,16), and mobilization of intracellular Ca 2ϩ (16). However, work from our laboratory and other laboratories has demonstrated that these signaling events are generally not related to cholesterol efflux but rather account for other potentially anti-atherogenic effects of HDL, such as stimulation of cell proliferation or inhibition of apoptosis (12)(13)(14)16). Moreover, induction of these signaling pathways is not linked to apoA-I but rather to active lipids carried by HDL (10 -14, 16).…”
Section: Fig 2 Inhibition Of Cdc42 Suppresses Apoa-i-induced Cholesmentioning
confidence: 99%
“…103 Although present on only one of 10 to 20 HDL particles, S1P contributes to several of the protective functions of HDL. For example, HDL-associated S1P appears to be important for the vasoprotective effects on endothelial cell survival, 104 109 and nitric oxide-dependent vasorelaxation. 20 It also inhibits vascular smooth muscle cell migration and chemokine production, 31, 110 cardiomyocyte apoptosis during hypoxia-reoxygenation, 111,112 and myocardial damage after ischemia/reperfusion.…”
Section: Sphingolipidsmentioning
confidence: 99%
“…It is important to note that the degree of eNOS activation by S1P is comparable to those attained by other classical eNOS agonists, including bradykinin or vascular endothelial growth factor (VEGF), suggesting quantitative importance of eNOS activation by S1P. 23,27 S1P has since been found to activate eNOS in many other cultured EC types, including human umbilical vein endothelial cells 28 (HUVEC) as well as bovine lung microvascular ECs. 25 In blood vessels isolated from rodent mesenteric arterioles and thoracic aorta, S1P activates eNOS via pertussis toxinsensitive G-protein-coupled receptor (GPCR) pathways.…”
Section: Cellular Sources Of Blood Sphingosine-1-phosphate That Modulmentioning
confidence: 99%